Model Tests on the Antibreaking Countermeasures for Tunnel Lining Across Stick-Slip Faults - Guang-yao Cui; Xue-lai Wang; Zheng-zheng Wang; Dao-yuan Wang (Advances in Materials Science and Engineering)
In order to improve the structural safety and stability of the tunnels crossing stick-slip fault, an indoor model test on the effect of tunnel antibreaking measures under the influence of fault stick-slip movements was conducted. Using contact pressure, longitudinal strain, and safety factor, the antibreaking effect of tunnels was compared and analyzed under 5 kinds of operating conditions, mainly including no measures, structural strengthening, structural strengthening and reducing dislocation layer, structural strengthening and reducing dislocation joint, structural strengthening and reducing dislocation layer, and reducing dislocation joint. The results showed that the longitudinal strain and contact pressure of the tunnel changed markedly (from severe change to more uniform change) when the reducing dislocation measures were adopted in the test, reducing dislocation layer/joint or reducing dislocation layer and reducing dislocation joint. The effect of reducing the fault stick-slip dislocation on the tunnel structure is very limited by only taking structure strengthening measures. The effect of reducing the fault stick-slip dislocation on the tunnel structure is obvious by using the reducing dislocation method, and the minimum safety factor is increased by more than 8 times. The effect of resisting and reducing the fault stick-slip dislocation on the tunnel structure is remarkable by adopting the measures of the structural strengthening and reducing dislocation layer and reducing dislocation joint, and the minimum safety factor is increased by more than 25.45 times. The results can provide reference for the design of antibreaking for the stick-slip fault tunnel in high earthquake intensity and dangerous mountainous areas.